Solving an inverse Cauchy Problem for modified Helmholtz Equations depending on a polynomial expansion approximation - shaimaa aamer; Fatima M. Aboud (Academic Science Journal)
In this study, a heat conduction in fin-related inverse problem for the modified Helmholtz equation is taken into consideration. The purpose of this study is to estimate the temperature on an under-specified boundary (a part of the outer border of a given domain) by using the Cauchy data, on a portion of the boundary that is accessible (boundary temperature and heat flux). The suggested meshless approach is used to numerically solve this problem. By injecting a noise to the Cauchy data, the stability is verified.